Development of E-LKPD Using Live Worksheets for Online Mathematics Learning during Covid-19 - Farman, Farman; Hali, Fitriyani; Rawal, Muhammad (Universitas Sembilanbelas November Kolaka, 2021)
This study aims to obtain e-LKPD using a valid, practical, and effective live worksheet on derived material. This type of development research aims to produce a product in the form of e-LKPD. The development of live worksheet-based e-LKPD is carried out through ADDIE design development steps consisting of analysis, design, development, implementation, and evaluation. The test subjects in this study were Class XI students at SMA Negeri 8 Kendari in 2021. The data collection instruments in this study consisted of a validation sheet used to determine the validity of the e-LKPD, a response questionnaire on the use of e-LKPD was used to obtain information on the practicality of e-LKPD, and learning outcomes tests to determine the effectiveness of e-LKPD. The results showed that (1) the validation results with an average score of 4.04 which means that the live worksheet-based e-LKPD is in very valid criteria and is feasible to use (2) The results of the analysis of student responses to the use of e-LKPD show that the average The student's class response is 80.3 which means the class response is positive and is included in the practical category. (3) There is a difference between the pre-test and post-test values, which means that there is an effect of using e-LKPD on learning outcomes. Thus the live worksheet-based e-LKPD is valid, practical, and effective.